Cadre conceptuel de qualification des entités de l'économie sociale dans les statistiques - Marie J. Bouchard; Paulo Cruz Filho; Martin St-Denis (Cadre conceptuel de qualification des entités de l'économie sociale dans les statistiques, 2015)
The starting point of the qualification of the social economy (SE) is that all definitions of the SE underline the primacy of the social purpose over the economic activity. This is especially shown in the empirical features which are typical of the structures and operation of the social economy and which distinguish it from the rest of the economy. This paper analyses some of the most important statistical studies on SE conducted by researchers, academic experts, public institutions and statistical agencies between 2005 and 2012. The resulting conceptual frameworks for doing statistics about the SE usually establish the type of entities, the legal status, sectors of activity that are excluded and a cluster of qualification criteria and their statistical indicators of social economy organizations. Typologies of organizations can also be established on other criteria such as the goals and missions or the modes of financing them. A conceptual framework for qualifying SE organizations should also allow assessing the peripheral components in this field and forecasting its own progress (for example, for the integration of new organizations which would further be acknowledged as being part of the social economy).
2575017-3; 635679337